2013
DOI: 10.1111/jphd.12036
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral health behaviors and status with depression: results from the Korean National Health and Nutrition Examination Survey, 2010

Abstract: Objective:To examine the association of depression with oral health behaviors and oral health status in a large nationwide sample of Korean adults. Methods: This study included 6,139 participants aged 19 years or older who participated in the fifth Korean National Health and Nutrition Examination Survey. Binary and polychotomous logistic regression analyses were used to estimate adjusted odds ratios (AORs) and 95 percent confidence intervals (CIs). Results: Participants with lifetime depression (self-report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 43 publications
5
55
0
1
Order By: Relevance
“…There are few studies about maternal depression and early childhood caries (ECC) [Seow et al, 2009;Finlayson et al, 2010]. Depressive symptoms have been associated with worse oral health-related behaviors [Anttila et al, 2006], and adults with lifetime depression have been reported to be more likely to have oral health problems than those without lifetime depression [Park et al, 2014]. Nevertheless, examining psychosocial maternal factors and the occurrence of ECC in their offspring in a sample of low-income Afro-American families, Finlayson et al [2010] did not find any association between depression in mothers and ECC in their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies about maternal depression and early childhood caries (ECC) [Seow et al, 2009;Finlayson et al, 2010]. Depressive symptoms have been associated with worse oral health-related behaviors [Anttila et al, 2006], and adults with lifetime depression have been reported to be more likely to have oral health problems than those without lifetime depression [Park et al, 2014]. Nevertheless, examining psychosocial maternal factors and the occurrence of ECC in their offspring in a sample of low-income Afro-American families, Finlayson et al [2010] did not find any association between depression in mothers and ECC in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and oral health issues are common problems in the general population; thus, the relationship between oral health and mental health must be elucidated to improve these factors in public. In particular, understanding the degree to which oral health behaviors affect the relationship between depression and oral health status is important for managing oral health in depressed patients [Park et al, 2014]. Parents, especially mothers, are widely acknowledged to play a pivotal role in the establishment of oral health-promoting behaviors that prevent the development of childhood dental caries [Hooley et al, 2012].…”
mentioning
confidence: 99%
“…Several studies have investigated this association using large data obtained from the Korea National Health and Nutrition Examination Survey (KNHANES) [5, 1416]. A study has reported on the effects of oral health behavior and status on the quality of life in the Korean elderly [5], and only a few reports have indicated that oral pain or oral health status is correlated with depression in Korean adults or the elderly [1416]. However, there is a lack of research on the influence of oral health status on stress, depression, and suicidal ideation-the primary markers of mental health-among Korean adults.…”
Section: Introductionmentioning
confidence: 99%
“…There have been three reports on the association between chewing difficulty and symptoms of depression . The Whitehall II study was a prospective closed‐cohort study with a small sample size (N = 227), and the results cannot be generalized .…”
Section: Discussionmentioning
confidence: 99%
“…The Invecchiare in Chianti study assessed only individuals aged 65 and older and did not adjust for well‐known confounders such as detailed oral health status or behaviors . A third study assessed this relationship in the Korean population but also did not adjust for systemic confounders and did not include an age‐ and sex‐stratified analysis . The results of these studies are consistent with findings of previous studies that link depression disorders to chewing problems, although it is difficult to compare the results of the current subgroup analyses with previous studies because few studies have examined the relationship between chewing difficulty and symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%